Finite element analysis of osteoporotic vertebrae with first lumbar (L1) vertebral compression fracture - Mazlan, M. H.; Todo, M.; Takano, Hiromitsu; Yonezawa, Ikuho (International Academy Publishing, IACSIT Press, 2014)
The aim of this work is to assess the biomechanical response or load transfer response between osteoporotic (with first lumbar (L1) vertebral compression fracture) and healthy vertebrae in five vertebral physiological motions namely as compression, flexion, extension, lateral bending and axial rotation. For this purpose, an image-based heterogeneous three-dimensional patient-specific of lumbar and thoracic spinal unit (T12-L2) finite element models for healthy and osteoporotic subjects were created. The finite element analysis have shown that one of the most significant effects of osteoporosis is the tendency to produce higher stress and strain in the cancellous region of the vertebral body. The maximum stress and strain was 4.53 fold (compression) and 5.43 fold (axial rotation) higher for the osteoporotic than the healthy subject, respectively, under the similar loading activity. Uneven stress distribution patterns also have been detected in the osteoporotic vertebrae rather than the healthy vertebrae. All of these characteristics are reflected by a reduced structural strength and bone mass which might lead to an increased risk of fracture. These results strengthen the paradigm of a strong relationship between osteoporosis and its high susceptibility to fracture.